TRAM SERVICE AS A FACTOR OF EVERYDAY LIFE IN THE SOVIET CITY OF MAGNITOGORSK - Potemkina, Marina; Makarova, Nadezhda; Pashkovskaya, Tatiana; Chernova, Nina; Popov, Maxim (Journal of Applied Engineering Science, 2020)
The tram service in Magnitogorsk is one of the main means of transportation. This study substantiates the cause-and-effect relationships of the tram service development and the industrial progress in Magnitogorsk. Due to the retrospective analysis of the transport infrastructure development singled out the tram service as a social factor in the cultural formation of an industrial society. By means of an abstract-logical method, based on factual historical evidence, the authors established that the authorities actively used trams to form the culture of citizens, to influence the nature of their social behavior. The periodization of the evolutionary change in people's behavior under the influence of the authorities when using trams to develop a positive attitude towards the industrialization of society is determined. The obtained results can be useful for the municipal authorities of Magnitogorsk to reassess the importance of tram service for modern society in the context of the displacement of this type of transport by the dynamic development of transport infrastructure.
Keywords: transport, tram services, transport infrastructure, industrialization, Soviet society.